Pengaruh Beban Kerja Dan Evaluasi Kinerja Pegawai Melalui E-Kinerja Terhadap Kinerja Pegawai Pada Dinas Kesehatan Kabupaten Nganjuk - Mimin Dwi Jayanti; Arisyahidin Arisyahidin; Sonny Subroto Maheri Laksono (Universitas Islam Kadiri, 2023)
The aims of this study were (1) to find out the effect of workload on performance in Nganjuk District Health Office employees (2) to find out the effect of performance evaluation on performance in Nganjuk District Health Office employees (3) to find out the effect of Eperformance on performance in Service employees Nganjuk District Health Office (4) Knowing the effect of workload on the e-performance of the Nganjuk District Health Office employees (5) Knowing the effect of performance evaluation on the e-performance of the c (6) Knowing that eperformance is a mediating variable between workload on performance at the Keywords: Workload, Performance Evaluation, E-Kinerja, Performance (7) Knowing motivation is a mediating variable between performance evaluation and performance on employees of the Nganjuk District Health Office.The type of research in this study of 135 people was survey research. Sample size (sample size). The research instrument used was a questionnaire. The analysis method used is inferential analysis with a path analysis approach.Based on the results of the research and discussion that has been done, the conclusions that can be drawn are (1) The results of the first hypothesis testing indicate that the workload variable on performance has a significant negative effect on performance. (3) The results of testing the second hypothesis indicate that the performance evaluation variable has a positive and significant effect on performance. (4) The results of testing the third hypothesis show that the e-performance variable has a positive and significant effect on performance. (5) The results of testing the fourth hypothesis show that the workload variable has a significant negative effect on e-performance. (6) The results of testing the fifth hypothesis show that the workload evaluation variable has a positive and significant effect on e-performance.(7) The results of the sixth hypothesis test show that the E-Kinerja variable is an intervening variable that influences workload on the performance of the Nganjuk District Health Office employees. (8) The results of testing the seventh hypothesis show that the E-Performance variable is an intervening variable that influences performance evaluation on performance.